POSTOPERATIVE COMPLICATIONS IN PATIENTS UNDERGOING THYROID SURGERY - Jovanovski-Srceva M; Kokareva A; Kartalov, Andrijan; Kuzmanovska B; Gavrilovska Aleksandra; Spirovski, Z; Kondov, G; CHolancheski, R; Crvenkova S; Mojsova M; Peneva, M; Stevic M; et al. (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University, Skopje, Macedonia, 2018)
Background and objectives: Postoperative complications from thyroid surgery are numerous and may be shown on different levels. Some of these complications may be detrimental for patients, so minimization of the risks should be always considered. We evaluated the postoperative complications in patients after surgery of the thyroid gland at the Clinic for Thoracic Surgery, Skopje. Material and method: In retrospective manner, all patients undergoing thyroid surgery during the one-year period (1. January- 31. December 2017) were evaluated. Patients were divided into two groups, whereas group ST included patients who underwent goiter removal and subtotal thyroidectomy while group TT included patients in who total thyroidectomy was done. In both groups we analyzed the demographic data and the occurrence of postoperative (in the first 48 hours) complications (stridor, hoarseness, hemorrhage, nerve dysfunction, tracheomalacia, hypocalcemia and the need for reintubation and tracheostomy). Results: Total data from 197 patients was evaluated. 120 patients had subtotal thyroidectomy while total thyroidectomy had 77 patients. Postoperative complications occurred in significantly larger number of patients in the TT group (64.9 vs. 40%). Hoarseness (8.4% vs. 18.5%), stridor (18.3% vs. 9.2%) tracheomalacia (5% vs. 1.2%) and hematoma (2.5% vs. 3.8%) occurred in respect to the groups. Hypocalcaemia occurred in significantly larger number of patients in TT group. Permanent nerve injury was found in one patient in the same group and tracheotomy was done only in one patient. Conclusion: Overall results from our study show that the complications after thyroid surgery occur in all patients who undergo thyroid surgery. However, more severe complications and outnumbered are complications in patients who undergo total thyroidectomy.
Keywords: complications; occurrence; thyroid surgery; total thyroidectomy